Substantiation of stable functional osteosynthesis for fractures of the femoral neck - Tyazhelov, Olexiy; Pirogov, Evgeny (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
The main cause of a large number of poor results (from 30 to 63 %) in cases of osteosynthesis of the medial femoral neck fractures is the inability to provide a stable fixation of fragments for the period, necessary for consolidation. Important role in the loss of a stable fracture fixation they consider process of edge resorption of bone fragments. Most authors recognize that the degree of shortening is different, but it is almost always the case. Ignoring of this phenomenon in experiments on human cadaver and in mathematical models inevitably leads to an error in the biomechanical rationale designs. The vast majority of internal fixators which compresses the device as planned, in practice are different variants of splinting. Purpose: theoretical justification of opportunities for optimum level of compression between the fragments in osteosynthesis of medial femoral neck fractures in conditions of marginal resorption of bone fragments. Methods: more than 200 patents having existing fixing devices for femoral neck fractures were analyzed. Results: the basic conditions for successful fixation of the medial femoral neck fractures were defined. The necessity of constant compression between the fragments as pledge of stable fixation and atraumatic technique of the operation were named by almost all authors as priority principles. Compression between the fragments causes the appearance of the friction force between them which ensures the stability of fixation. The value of compression between the fragments achieved during osteosynthesis with cancellous screws defined by the way of mathematical calculations. On the basis of Young's modulus for titanium screws and cancellous bone of the proximal femur approximate value of elastic deformation of the interacting materials while creating compression between the fragments was calculated. This gives an idea of minimal resorption leading to complete loss of compression between the fragments. Given the dynamics of marginal of resorption of bone fragments revealed rapid disappearance of compression in the next few coming hours after osteosynthesis. This necessitates the use of spring-loaded fixing devices. The principal feature of the spring-loaded fixing devices is the ability to create a secondary compression due to the potential energy of the compressed spring. Recommended by various authors range of values (from 300N to 1000N) indicates the need to use a fairly stiff spring, practical application of which is limited by the strength characteristics of the bone especially in osteoporosis. This makes the use of such fixing device practically impossible. Conclusions: stable fixation of medial femoral neck fractures may be realized only through the constant compression between the fragments. Values of minimum compression required in horizontal and vertical position of the body differ significantly (up to 100 and 1000 N, respectively.) Creation of fixing devices providing constant compression up to 1000 N is practically impossible. Thereby constructive solution of this problem we believe in use of spring-loaded fixing device with a spring force of about 100 N in conjunction with the mechanism for engaging a ratchet type, which fixes the fragments into the position of maximum rapprochement and prevents the formation of diastase in upright posture due to the rigid connection with distal fragment. This combination allows to reduce in ten times the level of minimally sufficient compression between the fragments up to 100 N without the risk of loss of stability of fixation.